MAKNA SIMBOL KOMUNIKASI DALAM TARI TOPENG SIDAKARYA - Inggra Swathy, I Dewa Ayu; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2020)
ABSTRACT Balinese dance is a form of non-verbal communication in which there are symbols that have meaning in them. This can be seen in one of the dances used as a facilitator of the ceremony of his yadnya in Bali, namely the Sidakarya Mask Dance. This study uses descriptive qualitative methods and uses the Theory of Semiotics Charles Sanders Peirce. The results of this study indicate that in the Sidakarya Mask Dance there are communication symbols that are shown through the movements, clothing, and property used. Broadly speaking, this dance movement shows the symbol of giving welfare to Hindus. Through clothing, this dance shows a symbol of authority, strength, and defense from enemy threats. While the properties in this dance show the symbol of spreading wealth and neutralizing negative aura. Key Words: Meaning of communication symbols, Semiotics, Sidakarya Mask Dance